CONFLICTS OF THE MAIN CHARACTER IN THE NOVEL “REEDEMING LOVE” BY FRANCINE RIVERS: A FREUDIAN PSYCHOANALYTIC APPROACH - Winni Mundung; dewi christa kobis; Maya Pinkan Warouw (Universitas Sam Ratulangi, 2025)
This research examines the conflicts experienced by the main character, Angel, in a novel entitled Redeeming Love by Francine Rivers, using a psychoanalytic approach grounded in Sigmund Freud’s theory of the id, ego, and superego (1923). The study aims to identify and classify the psychoanalytic elements within the narrative and analyze their implications on character development. Employing a descriptive qualitative methodology, the data for this research was collected from the scripts in the novel and then classified based on Freud’s theory as the foundation to analyze the conversations found in the scripts. The findings showed that Angel’s past experiences have shaped her into a woman who finds it difficult to trust others, particularly in romantic relationships with man. The relationship between Michael and Angel as well as Michael Hosea’s strong ego play. Crucial roles in mediating these conflicts are providing Angel with the love and support necessary for healing. These findings demonstrate that understanding the psychoanalytic elements offers deeper insights into the characters’ emotional struggles and their journeys toward self-acceptance and redemption.